Anpassad skötsel : exempel på hyggesfritt skogsbruk i Mellannorrland - Jansson, Lisa (SLU/Southern Swedish Forest Research Centre, 2007)
Total protection is often the option chosen when protecting forests with high environmental values. An alternative to total protection is application of management regimes that do not interrupt continuity of tree cover. This study focuses mainly on continuous cover forestry (CCF) in forest stands already protected. All objects are situated in the county of Jämtland in northwest Sweden. The purpose of the study was to attain a greater knowledge about CCF practices. Two issues were addressed. The first one was whether these methods are in accordance with regulations in the Swedish Forest Act regarding minimum post-harvest stocking levels. Secondly, to analyse these methods, i.e. to define them and describe residual stands resulting from their use. Extraction levels in the stands investigated were in accordance with the Swedish Forestry Act §10. Extraction rates ranged from 16 to 39% of the standing volume. Cutting cycles recommended range from ten to fifteen years. For one stand a cycle of some thirty years might be more suitable, because of the higher extraction rate in previous harvesting operations. Allowing local stand conditions to determine management regimes and cutting cycles is of course important. Three CCF regimes were detected. An important result in terms of conservation value was that diameter distributions were not changed by harvesting. This could imply that these methods are worth considering if the purpose is to preserve a certain environment regardless of whether it is conservational or recreational values that are to be preserved. Avsättning av skogsmark är ett viktigt, men också ett relativt vanligt redskap för att värna om den biologiska mångfalden. I de naturvårdsavtal som Skogsstyrelsen Mellannorrland upplåtit under lite drygt tio års tid, har så mycket som 64% lämnats till fri utveckling. Att avsätta all mark som har betydelse för den biologiska mångfalden är däremot inte i överensstämmelse med skogspolitikens ramar. Ett skogsbruk med utrymme för anpassade skötselåtgärder kan vara en ...